Aplikasi Sistem Inventory Barang Menggunakan Qr Code Scanner Berbasis Android Di PT. Jotun Indonesia - Ismasari Nawangsih; Rachmat Hidayat (Jurnal SIGMA, 2021)
At this time in the labeling section of PT. Jotun Indonesia often makes mistakes in conveying information to the filling section about can products that have been labeled, because in recording the list of products that have been labeled that are still labeled using manual methods, namely by writing on a whiteboard, of course, this method is less effective. Therefore an application is needed to find out which product can lists are already labeled so as to facilitate the labeling operator in effectively informing labeled product cans to the filling operators. The purpose of this research is to find out ways for labeling operators to input QR code labels automatically and to find out ways for labeling operators to inform the filling list of products that have been labeled to the filling operators effectively so as not to inhibit the filling process, and target filling per day is still achieved . The research method used is descriptive in nature with the OOP (Object Orientied Programming) approach while the system development method for android-based applications uses the prototype method. Making software in this thesis, the author uses PHP Framework Codeigniter, Sublime Text 3, Android Studio, and for the database using PhpMyAdmin. The result of making this application is to be able to check the status of the product list list of products that have been labeled via an android smartphone, by scanning the QR code in the box that contains the product can that has been labeled using the system application. Testing of this application uses blackbox testing. This research shows that the application of goods inventory system using Android-based QR code scanner can facilitate the labeling operator to input QR code label identity data automatically, helping to facilitate the labeling operator to convey labeled product list information to label operators effectively. Keywords : Aplikasi, Inventory, QR Code Scanner, Android.